When Scientists and Industry Technologies Mitigate Habitat Loss: The First Bioconstruction Relocation in the Mediterranean Sea - Casoli, Edoardo; Ventura, Daniele; Mancini, Gianluca; Belluscio, Andrea; Ardizzone, Giandomenico (Frontiers in Marine Science, 2022)
The need for habitat recovery in coastal areas, especially those subjected to intensive exploitation, has increased because of significant historical loss and alteration of habitats and, therefore, adverse ecological impacts. The present study defines a stepwise approach to mitigate habitat loss in deep coastal environments, describing the planning, intervention, and monitoring phases following the Trans Adriatic Pipeline (TAP) laying along the Apulian coast (Adriatic Sea, Italy). Preliminary field activities encompassed morpho-bathymetric data (MBES and SSS), SCUBA and ROV observations to accurately map and characterize the mesophotic reefs built by invertebrates found in the area. The pipeline route interfered with 30 outcrops between 50 and 80 m depth, mostly colonized by 15 taxa/morphological groups. A functional/conservative approach was adopted to recognize the taxa/morphological groups on which to focus the removal and following relocation activities based on their abundance, conservation status, and functional traits. Saturation divers teams, ROV pilot technicians, and researchers collaborated to minimize the physical impact and the loss of organisms due to the pipeline installation. They relocated a total of 899 living portions (nuclei) from the 30 interfered reefs on the top of the pipeline. The following monitoring activities, carried out after fourteen months since the intervention, revealed a high mean survival rate (88.1%) and slight variations in the structure of the nuclei assemblages. This study represents a paradigmatic case of involvement and support of the private oil and gas sector to mitigate habitat loss in the Mediterranean Sea, and stresses the need for integrated management involving different stakeholders to mitigate the effects of the exploitation of marine resources through ante operam assessment and active restoration actions.